2013
DOI: 10.3182/20131120-3-fr-4045.00009
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the HOG detector in the UAV context

Abstract: The well known HOG (Histogram of Oriented Gradients) of Dalal and Triggs is commonly used for pedestrian detection from 2d moving embedded cameras (driving assistance) or static cameras (video surveillance). In this paper we show how to use and improve the HOG detector in the UAV context. In order to increase the elevation angular robustness we propose to use a more appropriate training dataset and sliding windows. We show results on synthetic images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Blondel et al showed that the robustness to the elevation angle can be improved on synthetic images by a multi-view training at different elevations [16]. When the elevation angle is greater than 45degrees significantly better results were obtained for detecting 3d models.…”
Section: A a More Appropriate Datasetmentioning
confidence: 99%
“…Blondel et al showed that the robustness to the elevation angle can be improved on synthetic images by a multi-view training at different elevations [16]. When the elevation angle is greater than 45degrees significantly better results were obtained for detecting 3d models.…”
Section: A a More Appropriate Datasetmentioning
confidence: 99%
“…It is of great interest to users and scientists to develop systems for the rapid identification of injured persons following natural disasters in unmanned aerial vehicles (UAV) images (Jingxuan et al, 2016). Unfortunately, when UAV images are used for human sensing with other challenges, the use of a UAV as an image platform introduces certain other problems (Blondel, 2013). Because pictures are taken from above, individuals can be quite different from those on the ground.…”
Section: Introuctionmentioning
confidence: 99%